Fabrication of 2D sheet-like BiOCl/carbon quantum dot hybrids via a template-free coprecipitation method and their tunable visible-light photocatalytic activities derived from different size distributions of carbon quantum dots. (18th December 2015) - Deng, Fang; Lu, Xiaoying; Zhong, Fei; Pei, Xule; Luo, Xubiao; Luo, Shenglian; Dionysiou, Dionysios D; Au, Chaktong
Abstract: A series of two-dimensional (2D) interlaced BiOCl/carbon quantum dot composites (denoted as BiOCl/CQD composites) were synthesized by a template-free coprecipitation method at room temperature, and the influence of different particle size distributions of the CQDs on the physiochemical properties and photocatalytic activities of the BiOCl/CQD composites was studied. CQDs can change the morphology and increase the specific surface area of the BiOCl/CQD composites. Moreover, the particle size distribution of the CQDs (CQD loading amount) has some effect on the light absorption, separation of photogenerated charge carriers, and photocatalytic performance of  the BiOCl/CQD composites. The optimized size distribution of the CQDs is 50–150 nm. BiOCl/CQD (50–150 nm) composites showed the best improvement of light absorption and the highest photocurrent density of 0.44 μ A cm −2, and exhibited the highest photocatalytic activity with almost 100% 2-nitrophenol removal under visible-light irradiation. The high efficacy of BiOCl/CQD (50–150 nm) composites could be attributed to their excellent light absorption and highly effective separation of photogenerated charge carriers.